STUDY OF LEIDENFROST MECHANISM IN DROPLET IMPACTING ON HYDROPHILIC AND HYDROPHOBIC SURFACES - KIM, SEOL HA; KANG, JUN YOUNG; AHN, HO SEON; JO, HANG JIN; KIM, MOO HWAN (International journal of air-conditioning and refrigeration, 2013)
Water droplets, 2 mm in diameter, were allowed to fall freely onto hydrophobic and hydrophilic heated surfaces, and their impacts were imaged using high-speed cameras to investigate the droplet dynamics and heat transfer. As the heating power increased, the water droplets evaporated faster, eventually hovering over the surface due to the formation of a boiling film when the Leidenfrost point (LFP) was reached. The heat transfer from the surface into the droplet was evaluated, and LFP transition phenomena were investigated using time-resolved imaging of both side and bottom views. The hydrophilic surface showed a higher heat transfer rate and a higher LFP than the hydrophobic surface did. Furthermore, the droplet dynamics revealed very different shapes depending on the surface wettability; vigorous bubble nucleation and growth was observable for the hydrophilic surface, but not the hydrophobic surface. The rebound behavior of the droplets was analyzed based on the droplet free energy, including kinetic, potential, and surface energy terms.